Holparti (Holistic Postpartum Class Murti) to increase the self-efficacy of postpartum mothers - Murti Ani; Yanik Muyassaroh; Marlynda Happy Nurmalita Sari (Jurnal Kesehatan Ibu dan Anak, 2022)
The postpartum period is a time when mothers are required to be able to start their new duties and roles. Holistic care is needed for postpartum mothers, including care for physical, and psychological needs, and support for the social, spiritual, and cultural environment. The purpose of this study was to determine the effectiveness of Holparti (Holistic Postpartum Class Murti) on the self-efficacy of postpartum mothers. This research is a quasi-experiment with a Posttest Only Control Group Design with a cross-sectional sampling technique using simple random sampling, with a sample size of 31 for the control group and 31 for the treatment group. Measurement of self-efficacy was carried out on the 7th day of postpartum using a questionnaire. The validity and reliability test using Product Moment Test and Cronbach's Alpha. Analysis of research data using independent t-test. The result of the independent t-test obtained a p-value of 0.000 (<0.05), so there was an effect of Holparti on the self-efficacy of postpartum mothers. Holparti is effective in increasing the self-efficacy of postpartum mothers.